The Effect of Epidemiologist Explorations Gamification to Increase Children's Health Knowledge - Diah Adni Fauziah; Nunik Triyani; Rifa Nailufar (GLOBAL HEALTH SCIENCE GROUP, 2025)
Generational change can be interpreted as educational development, including changes in educational strategies so that education is carried out more effectively and efficiently. One approach that suits the character of learning in the 21st century is through gamification, namely game-based learning. Objective: Exploring Epidemiologists was a game approach based on introducing the Epidemiology profession which aimed to increase children's health knowledge. Method: This research used a quasi-experimental pre-post one study design. Samples consisted of 17 respondents, children aged 8-10 years who took part in the Epidemiologist Exploration activity. Data were analyzed using the Wilcoxon Test to see the results of pre and post intervention knowledge. Results: The results of the research showed that there was no effect of Epidemiologist Exploring gamification on increasing children's health knowledge (p=0.755). Conclusions: The gamification process in children's health education should pay attention to environmental confounding factors found by respondents.